Has the Eurozone Become Less Fragile? Some Empirical Tests - Paul De Grauwe; Yuemei Ji (Center for Economic Studies and ifo Institute (CESifo), 2015)
In this paper we provide empirical evidence documenting the nature of the Eurozone's fragility. We find that during periods of turmoil, financial markets have tended to impose strong programs of austerity on member countries of the Eurozone. This confirms the evidence we found in a previous paper (De Grauwe and Ji(2013)). In addition we find that the panic-induced austerity, as it occurs mainly during periods of recession, has the effect of reducing the power of the automatic stabilizers in the government budgets, thereby making the economic downturns more intense. We find evidence that this feature has been present in the Eurozone. Our policy conclusion is that the institutional changes that have been introduced in the Eurozone since the start of the sovereign debt crisis are insufficient to safeguard the Eurozone from future crises.
Keywords: E40; 330; Eurozone; austerity; automatic budget stabilizers